Degradation of monocrotophos in cardamom under field conditions and during processing - Natarajan, J Thomas, X Reivax, M Oommen, J J Varghese, P (Journal of Spices and Aromatic Crops, 2016)
The degradation pattern of monocrotophos (Dimethyl (E) -1-methyl-2-(methyl carbamoyil) vinyl phosphate) in small cardamom (Elettaria cardamomum) under field conditions and during processing were studied. Monocrotophos 36% SL was sprayed at the recommended dose of 0.072% as per standard foliar application procedures. The residues were determined by gas chromatography with flame photometric detector. The degradation of monocrotophos followed first order kinetics and the half life of monocrotophos in fresh cardamom capsules was found to be five days. Due to dehydration during processing of fresh cardamom capsules, monocrotophos residue in cardamom capsule was found to be magnified by 3.5 times. Monocrotophos residue was reduced by 11.5% on curing and 29.5% on polishing.